PENINGKATAN KOMPETENSI PEDAGOGIK GURU DALAM MEMBUDAYAKAN NILAI-NILAI RELIGIUS - Agus Arifandi; Fathan Fihris (Jurnal Tinta, 2021)
Pedagogic competence is the ability to manage student learning including understanding students, designing and implementing learning, evaluating learning outcomes, and developing students to actualize their various potentials. The pedagogic competence of a teacher is the main reference for inculcating religious values. It is appropriate to be able to implement religious values ??when a teacher already has adequate pedagogical competence to absorb the transfer of character given by a teacher. Many things that a teacher must apply when instilling religious values ??to students include Power Strategy, Persuasive Strategy, Normative re-educative. We can see that the internalization of religious values ??has been going well by understanding its characteristics, namely: learning to live in differences, building mutual trust (mutual trust), maintaining mutual understanding (mutual understanding), upholding mutual respect (mutual respect), open in thinking, appreciation and interdependence, conflict resolution and violent reconciliation.